Collaboration across disciplines for the health of people, animals and ecosystems proceedings of the EFMI Special Topic Conference 2024 - Stoicu-Tivadar, Lăcrămioara; Benis, Arriel; Deserno, Thomas M. 1966- (IOS Press, 2024)
Intro -- Title Page -- Preface -- About the Conference -- Contents -- Section 1. One Digital Health and Climate Change -- Mapping of Health System Performance Indicators to the WHO HSPA Framework -- Frameworks and Tasks Used in Usability Testing Scripts: A Scoping Review -- ALSATION Study Protocol: Romanian Translation of Three Health Literacy Surveys -- Integrating Clinical Data and Patient-Reported Outcomes for Analyzing Gender Differences and Progression in Multiple Sclerosis Using Machine Learning -- Digital Applications Supporting Speech Therapy: Speech Therapists and Parents Insights -- Scaling up Environmental Governance in Precision Forestry -- Digital Twin Types and Applications in Healthcare -- Section 2. Health Informatics Education and Interprofessional Collaboration -- Achieving Digital Medicine Learning Outcomes Through an Interdisciplinary Course: A Pilot Study -- Collaboration Across Disciplines to Integrate Clinical Expertise into Medical Software Development: The Approach of the Dedalus Medical Office -- Preparing for Hospital at Home: A Review of the Current Landscape of Training Practices -- Organizing an Interdisciplinary Platform for Knowledge Sharing on a Class of Compounds of Natural Origin -- Supporting Pharmacist-GP Collaboration in Medication Review Using Argumentation -- Section 3. Healthcare Information Systems -- Mobile Health Technologies and Their Features Affecting Medication Adherence Among Cancer Patients: A Scoping Review -- Designing a User-Friendly Data Request Management System for a Growing Health Data Network - A Case Study in the AKTIN Registry -- The Pediatric Growth Hormone Deficiency Patient Journey: Identifying Opportunities for Digital Health Interventions -- Use Technology to Help Medical Staff Treat "New Health Problems" Arising Constantly.
Open Access
Keywords: Konferenzschrift